back to *Algebra*
# First Degree Equation Examples

### First Degree Equation Example 1

### First Degree Equation Example 2

- Question
- Solve the following equation:
- 3 ( x - 1 ) - 2 ( 3 x - 1 ) = 2 ( 3 - x )

- Solution
- 3(x - 1) - 2(3x - 1) = 2(3 - x)
- remove parenthesis
- 3x - 3 - 6x + 2 = 6 - 2x
- move variables to the left side of the equation and move numbers to the right side of the equation
- 3x - 6x + 2x = 3 - 2 + 6
- -x = 7 (divide by -1 on both side of the equation)
- x = -7
- therefore, x = -7 is the solution of given equation.

Substitute the x = -7 into the original equation, we will find that the left side of the equation is equal to the right side of the equation. Then x = -7 is satisfy the equation. So x = -7 is the solution of the given equation.

- Question
- (x - 1)/3 - (x + 1)/2 = 1
- solve this equation

- Solution
- (x - 1)/3 - (x + 1)/2 = 1
- both side of the equation multiply 6 to remove denominator
- 6 [(x - 1)/3 - (x + 1)/2] = 6 × 1
- 6 (x - 1)/3 - 6 (x + 1)/2 = 6
- 2 (x - 1) - 3 (x + 1) = 6
- 2x - 2 - 3x - 3 = 6
- keep the variables in the left side of the equation and move the numbers to the right side of the equation
- 2x - 3x = 2 + 3 + 6
- -x = 11
- both sides divide by -1
- x = - 11
- so x = -1 is the solution of the given equation

© Acceler LLC 2022 - www.mathtestpreparation.com